2000
DOI: 10.1001/archotol.126.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Difficulty Following Bismuth Subgallate Aspiration

Abstract: Bismuth subgallate, an agent that initiates clotting via activation of factor XII, has been advocated for use in controlling bleeding during tonsillectomy and adenoidectomy. Direct aspiration of bismuth has produced pulmonary complications in laboratory animals, but no clinical correlation in humans has been previously described. We report 2 cases of bismuth aspiration that resulted in respiratory difficulty after tonsillectomy and adenoidectomy. Neither child's respiratory compromise required airway intubatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…As an additional complication, respiratory distress has been reported due to bismuth subgallate when used to control hemostasis during tonsillectomy and adenoidectomy [21].…”
Section: Discussionmentioning
confidence: 99%
“…As an additional complication, respiratory distress has been reported due to bismuth subgallate when used to control hemostasis during tonsillectomy and adenoidectomy [21].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of BIPP-related complications, direct bismuth aspiration has been reported 35 to cause pulmonary complications in laboratory animals, but no clinical correlation in humans had been previously described until Murray et al 35 reported two pediatric cases of bismuth aspiration leading to respiratory difficulties after tonsillectomy and adenoidectomy; neither child's respiratory condition necessitated airway intubation. With that in mind, the application of BIPP, like all topical medications, must be performed with caution and following proper guidelines to minimize potential risks.…”
Section: Evaluation Of Wound Healingmentioning
confidence: 99%
“…In the United States, BSG is an active ingredient in Devrom® (internal deodorant), an over-the-counter FDA-approved medicine [62]. The side effects of BSG include temporary darkening of the tongue and risk of foreign body response that may result in acute pneumonia [157, 164]. Due to BSG’s possible hypersensitivity to the substance, hepatic or renal impairment is the caution impeding its application in patients with liver or kidney disease [157].…”
Section: Main Text: Topical Biomaterials Used For Pthmentioning
confidence: 99%